Optimalisasi Penggunaan Buku KIA untuk Peningkatan Perkembangan Kesehatan Ibu dan Anak - Louis, Stephanie Lexy; Mirania, Ayu Nina; Yuniarti, Evi; Manurung, Aprida (Universitas Kristen Indonesia Toraja, 2023)
The low understanding of mothers regarding the use of the Maternal and Child Health Book (KIA Book) is one of the factors contributing to the failure in implementing the Sustainable Development Goals (SDGs) program aimed at reducing maternal and child mortality rates. The role of midwives working together with community health volunteers has a six-fold greater influence on the community in raising awareness about the use of the KIA Book, thus providing more health-related information. The objective of this activity is to enhance motivation and improve mothers' knowledge in optimizing the KIA Book. This community engagement activity took place in RT 10 RW 03, Sukarami Village, Palembang City. The method employed involved participants completing a questionnaire to assess their understanding before and after receiving education through counseling. The results showed that there was an increase of 15 people (88.23%) falling into the good category and 2 people (11.76%) falling into the satisfactory category, indicating that the activity was successfully received and understood by the participants.